Giving a Voice to Nurse Managers and Staff Nurses: A Two-Centres Multi-Method Research Protocol to Optimize Nurses’ Actual Scope of Practice - Déry, Johanne; Paquet, Maxime; Boyer, Louise; Folch, Nathalie; Lavoie-Tremblay, Mélanie; Lavigne, Geneviève (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2023)
Introduction: Numerous studies have revealed that a limited time is devoted to value-added care activities that are part of nurses’ professional role (Déry et al., 2022). This has an impact on the performance of healthcare systems in terms of overall costs. The COVID-19 pandemic has put more pressure on healthcare organizations, on its nurse managers (NMs) and staff nurses.Objective: To mobilize key players in care units to propose effective and realistic strategies to facilitate the optimal deployment of nursing practice.Methods: This international research program encompasses 3 consecutive cross-sectional studies involving 2 healthcare centres: 1 in Canada and 1 in Switzerland. Study 1’s qualitative design will include focus groups with NMs. Study 2’s quantitative correlational design will survey staff nurses. Study 3 will include multiple meetings with NMs, staff nurses, clinical nurse specialists and educators (key players) to develop a logic model of intervention to propose effective and realistic strategies to facilitate the full deployment of nurses’ scope of practice.Discussion and Research Spin-offs: Study 1 will help describe the innovative management practices of NMs since the onset of the COVID-19 pandemic and identify their support and educational needs. Study 2 will explore the perceptions of staff nurses regarding the work psychological climate and work recognition, their actual scope of practice, their professional satisfaction at work and their perception of the quality of care. Study 3 will take advantage of this new data and mobilize key players in the identification of improvement strategies adapted to their own reality.